Electrical and thermal properties of high aspect ratio carbon-based polymer nanocomposites - Aliskanovic, Emil (My University, 2018)
This project is a part of a collaboration of Borealis AB Stenungsund with Chalmers University of Technology. The objective of this project is to conduct an experimental study on the effect of different carbon based high aspect ratio fillers and different polymer architectures on the resulting thermal, electrical and morphological properties. A literature review was performed on the methods of analytical characterization, results of thermal and electrical properties for similarly used materials in this project. A deeper analysis has been made on the percolation theory which is the quintessential driving factor of the high aspect ratio fillers on the electrical properties. Parameters like filler type, polymer matrix, dispersion method, filler ratios and blend ratios are evaluated with respect to their impact on percolation threshold, degree of crystallinity, thermal stability, melting and crystallization temperature. Regarding the electrical properties of hybrid filler composites, it showed to have a synergetic effect when substituting 10 wt.% with another type of filler with different dimensionality. This was shown to be the case for three different hybrid systems. The degree of crystallinity was observed to have a parabolic trend where when combining certain fillers with each other. It was found that at equal parts of two different fillers, there was a maximum in the degree of crystallinity. Substituting 10 wt.% of a certain filler type showed to improve electrical properties that may be used in commercial applications to lower the cost of certain products. For further studies, a more in-depth analysis of the relationship between the different fillers could perhaps result in a better hybrid composite.
Keywords: Materialteknik; Nanoteknik; Materials Engineering; Nano Technology